2010
DOI: 10.1007/s12186-010-9042-5
|View full text |Cite
|
Sign up to set email alerts
|

Seizing Workplace Learning Affordances in High-Pressure Work Environments

Abstract: Work in call centres is often presented as a form of unskilled labour characterized by routinization, technological surveillance and tight management control aimed at reaching intensive performance targets. Beyond delivering business objectives, this control and efficiency strategy is often held to produce counterproductive effects with regard to employee well-being and the quality of customer interactions. Yet, almost contrarily, based on evidence from ethnographic field data from a call centre for sales and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In our study we participated on a daily basis in the work at the unit of analysis in a period of four months, gathering data both by observing, questioning and participating in the actual work at the unit of analysis, resulting in a first hand understanding of the full work processes and the culture in which the work was done (cf. also Gnauer, 2010). During the action research process we made several interventions with staff and management based on a learning dialogue, where the existing work processes were critically reflected upon (ibid.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we participated on a daily basis in the work at the unit of analysis in a period of four months, gathering data both by observing, questioning and participating in the actual work at the unit of analysis, resulting in a first hand understanding of the full work processes and the culture in which the work was done (cf. also Gnauer, 2010). During the action research process we made several interventions with staff and management based on a learning dialogue, where the existing work processes were critically reflected upon (ibid.).…”
Section: Methodsmentioning
confidence: 99%
“…The new dimension combined with our four-month clinical-inquiry action-research methodology (Bradbury and Rearson, 2008;Gnauer, 2010) has resulted in unique multidimensional data which through our analysis gives us new important perspectives for organisational development and allows us to avoid a one-dimensional perspective on innovation, as criticised by Anderson et al (2004) and Fagerberg (2005). As a result, we set up as hypothesis that the application of learning styles can positively affect individual learning, and thereby enhance collaboration and communication in a group/team context, resulting in the incremental process innovation we refer to as organisational development.…”
Section: Introductionmentioning
confidence: 99%
“…Grant and Spivey (2003) indicated that cognitive processing is sometimes the result of attention and eye movements, so expert gaze replay may improve skilled thinking (Kuhn 2009). Finally, interacting with digital media, such as computer-based gaze replays, can increase trainee motivation, interest, and engagement, particularly through situational affordances, which function as important precursors for work-related learning (Hidi 2006;Gnaur 2010). To summarize, analysis of eye movement differences may inform the design of learning environments to include viewing the scan paths of experts for directing the attentional resources of novices.…”
Section: Implications For Theory Developmentmentioning
confidence: 99%
“…The current debate on workplace learning emphasises the significance of individual biography (e.g., Hodkinson et al 2004;Hodkinson 1995), individual motivation in the workplace (Evans et al 2006;Evans et al 2004), and the interdependencies between individual attitudes and informal learning in the workplace (Eraut 2004). Individual expectations and attitudes are therefore perceived as motivating factors which are strongly related to the process of identity construction in the workplace and beyond (Gnaur 2010). The individual perspective on knowledge and learning as well as individual experiences in the workplace, as argued by Michael Eraut (2004), contribute to shaping the ways in which learners experience their environments (either formally or informally) and avail of new learning opportunities.…”
Section: Individual Engagement Through Boundary Crossingmentioning
confidence: 99%